Turning to the causes (Actual Problems of Psychology in Educational Institutions, 2023)
Neither classical philosophy nor modern physics has yetprovided a convincing answer to the question of the origins of being.The author believes that this state is caused, on the one hand, by anexcessive preoccupation with expensive empirical research and, on theother hand, by an excessive preoccupation with sometimes too abstrusemathematical constructs at the expense of a simple but careful analysis ofpossible mechanisms underlying the root cases of existence
Keywords: ontology, epistemology, methodological levels, prime cause, substantive unit, spherical construction, division of the substantive particle